Urgensi Peran Pemimpin dalam Manajemen Perubahan di Lingkungan Organisasi Pendidikan Islam: Sebuah Analisis Konseptual - Suandi, Ari (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This study aims to analyze the urgency of the leader's role in change management within the Islamic educational organizational environment, focusing on understanding the dynamics of organizational change, factors influencing resistance to change, and effective strategies for reducing such resistance.Method – Employing a conceptual analysis approach, this research outlines key concepts such as